Ibalizumab Targeting CD4 Receptors, An Emerging Molecule in HIV Therapy - Iacob, Simona A.; Iacob, Diana G. (Frontiers in Microbiology, 2017)
The HIV infection is responsible for the most devastating global pandemic of the last century. More than 39 million people have died of HIV/AIDS since 1981.The history of the antiretroviral (ARV) treatment begins with the discovery of zidovudine a nucleoside reverse transcriptase inhibitor. This breakthrough was followed by other ARV drug classes and representatives. Presently the HIV treatment employs 27 ARV representatives belonging to five different classes. Despite the overt advantages of the ARV treatment and its long-term control of the HIV infection, there is increasing concern over the numerous adverse effects and resistance to current ARV drugs. Therefore the new HIV treatment strategies focus on the development of new ARV agents with a high genetic barrier to resistance and low toxicity. Monoclonal antibodies belong to a new drug class with encouraging results in the treatment of cancer, autoimmune disorders and most recently against HIV infection. The advantages of using monoclonal antibodies for HIV treatment are related to their antiviral effect, lack of toxicity, good resistance profile, additional synergy with other ARV drug classes and ability to restore the CD4 T-cell responses. The current article is a short summary of ibalizumab, an anti-CD4 monoclonal antibody that interferes with HIV viral entry. Current studies on ibalizumab have underlined its antiviral effect, minimal adverse effects and lack of crossed resistance with other ARV agents thus supporting its further therapeutic use in multidrug resistant HIV-infected patients.